Assessing the usefulness of clostridia spores for evaluating sewage sludge hygienization. (February 2017) - Martín-Díaz, Julia; Ruiz-Hernando, Maria; Astals, Sergi; Lucena, Francisco
Graphical abstract: Highlights: Clostridia and E. coli were monitored during sewage sludge anaerobic digestion. Results question the usefulness of clostridia as sewage sludge treatment indicators. Alkali pre-treatment (35.3 g NaOH/kg TS; 24 h) increased clostridia levels. Clostridia also increased after digesting NaOH or ultrasound pre-treated sludge. E. coli levels did not increase under any of the tested conditions. Abstract: The capability of clostridia spores to act as pathogen indicators in sewage sludge treatment was investigated. Sulfite-reducing clostridia and E. coli levels were monitored during waste activated sludge pre-treatments (alkali and ultrasound) and its subsequent mesophilic anaerobic digestion. E. coli was maintained or reduced depending on treatment type and intensity. However, alkali pre-treatment (35.3 gNaOH/kg TS) by itself and alkali (157 gNaOH/kg TS) and ultrasound (27, 000 kJ/kg TS) pre-treatments followed by anaerobic digestion provoked reproducible clostridia increases. Specifically, up to 2.7 log10 after 35.3 gNaOH/kg TS pre-treatment and up to 1.9 and 1.1 log10 after digesting the 157 gNaOH/kg TS and 27, 000 kJ/kg TS pre-treated sludge, respectively. Having rejected the hypotheses of sporulation and floc dissipation, the most plausible explanation for these clostridia increases is re-growth. These results question the suitability of clostridia spores as indicators of sludge treatment and other biological treatments where clostridia may have a role.